The contributions of nature to people within the Yawuru Indigenous Protected Area. Issue 6 (17th April 2019) - Newman, Benjamin; Wilson, Kerrie A.; Melbourne, Julie; Mathews, Dean; Wysong, Michael; Iacona, Gwenllian D.
Abstract : Managers of Indigenous Protected Areas (IPAs) may need to communicate the value provided by their protected area to indigenous and nonindigenous stakeholders, especially if a political focus on maximizing economic opportunities conflicts with traditional priorities. To facilitate this process, we used the latest Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services conceptual framework and the IPA plan of management to identify the diverse ways that nature contributes to people in the Yawuru IPA (Western Australia). 68 out of 144 of the IPA management objectives related directly to ecosystem goods and services of which 65 are nonmaterial, 35 material, and 24 regulating (some services overlap). As a guide for management to assess relevant contributions, we identified valuation methods applicable to the IPA's wetlands and found that a wide range of options are available to assess ecosystem value. We also performed a detailed assessment of fresh water flow over the IPA.